Structural Equation Model of the Factors Affecting Construction Industry Innovation Success - Demirdogen, Gokhan; Isik, Zeynep (TURKISH CHAMBER CIVIL ENGINEERS, 2021)
Innovation is seen as one of the major factors to improve construction industry despite conventional structure of the industry impede implementation of its practices. A convenient solution to promote innovation or force the companies to adopt it, is the legal regulations that can be set forth by the decision makers of whom aware and prevailed of the macro benefits of innovation practices. However, the impact of innovation practices on industry indicators was not defined adequately to understand those benefits. This study aims to reveal the relationship between company-level innovation success measures and industry-level innovation success indicators. Therefore, a comprehensive literature review was performed to determine those success measures and indicators and the results were validated with an illustrative case study. The outputs of the case study was used to construct structural equation model exhibiting the interdependencies between factors. The study results approved that there is a significant relationship between the innovation practices of construction companies and construction industry innovation. According to the results, increase in competitive advantage among rivals and improved reputation were seen as the two highest indicators in the company-level. Additionally, the study showed that the most important innovation success indicator at the industry-level was found as employment and new job opportunities.
Keywords: Innovation; structural equation modeling; building information modeling; construction industry; BIM; IMPLEMENTATION; PERFORMANCE; TECHNOLOGY; BENEFITS; BUSINESS; DRIVERS; Engineering